A transcription aptasensor: amplified, label-free and culture-independent detection of foodborne pathogens via light-up RNA aptamers. Issue 68 (5th August 2019) - Sheng, Lele; Lu, Yunhao; Deng, Sha; Liao, Xinyu; Zhang, Kaixiang; Ding, Tian; Gao, Hong; Liu, Donghong; Deng, Ruijie; Li, Jinghong
Abstract : We report a light-up RNA aptamer-based transcription aptasensor, enabling sensitive, label-free and culture-free detection of intact foodborne pathogens. Abstract : We report a transcription aptasensor by using a light-up RNA aptamer. It allows for sensitive, label-free and culture-free detection of intact foodborne pathogens, and no separation, purification or enrichment processes are involved.